Phytotherapy in the context of Polycystic Ovary Syndrome: A narrative review (Research, Society and Development, 2024)
The use of medicinal plants for therapeutic purposes has records that may date back to 60,000 years BC, and Phytotherapy is used for various types of treatment in women's health, such as in Polycystic Ovary Syndrome (PCOS). PCOS is an endocrine, metabolic, and reproductive disorder that affects women of childbearing age. It is known that in addition to the synthetic drugs used to aid in the treatment of PCOS, a balanced diet and the practice of physical activities are great allies in the management of this syndrome, in addition, some medicinal plants can be used to contribute to the effective management of PCOS. The objective of this research was to review the literature, on species that have properties capable of positively influencing the metabolic and hormonal profile of patients with PCOS. This is a narrative review of the literature, whose searches were carried out in the Scielo, PubMed, and Google Scholar databases. The most frequently found species with applicability in the context of PCOS were cinnamon (Cinnamomum verum), saffron (Curcuma longa), marjoram (Origanum marjoram), fennel (Foeniculum vulgare Mill.) and soy isoflavones (Glycine max). Despite the benefits regarding metabolic and endocrine profiles with the use of such plant species, more clinical and experimental studies applied on this topic are necessary to better define the dosages and safety profiles of these medicinal plants with the potential to be used in the management of PCOS.